2007
DOI: 10.1007/s00467-007-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of fetal hydronephrosis

Abstract: Prenatally detected hydronephrosis has become a common diagnosis for both pediatric nephrologists and urologists. Hydronephrosis is most commonly assessed by the Society for Fetal Urology grading system or anterior-posterior diameter of the renal pelvis in the transverse plane. Some cases of bilateral obstruction, most commonly from posterior urethral valves, can be life-threatening and require close monitoring or, occasionally, fetal intervention. The majority are unilateral and of no threat to the growing fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 62 publications
0
32
1
6
Order By: Relevance
“…Mami et al reported a prevalence of VUR grade I-III of 1.8% in infants with isolated persistent hydronephrosis up to 15 mm without analyzing if they had bilateral or unilateral hydronephrosis [11]. Most authors suggest performing early postnatal imaging in NBs with bilateral HN without differentiating the hydronephrosis grade [13][14][15][16]22]. The usual clinical concern in NBs with bilateral hydronephrosis, especially in male NBs, is the posterior urethral valve (PUV), which is the most common cause of lower urinary obstruction in male NBs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mami et al reported a prevalence of VUR grade I-III of 1.8% in infants with isolated persistent hydronephrosis up to 15 mm without analyzing if they had bilateral or unilateral hydronephrosis [11]. Most authors suggest performing early postnatal imaging in NBs with bilateral HN without differentiating the hydronephrosis grade [13][14][15][16]22]. The usual clinical concern in NBs with bilateral hydronephrosis, especially in male NBs, is the posterior urethral valve (PUV), which is the most common cause of lower urinary obstruction in male NBs.…”
Section: Discussionmentioning
confidence: 96%
“…NBs with bilateral hydronephrosis, especially male NBs, are considered to be a group with a higher risk of having a significant abnormality and/or impairment of postnatal renal function [12]. Most papers state that patients with bilateral hydronephrosis should undergo voiding cystourethrography (VCUG) [13][14][15], and the Society for Fetal Urology consensus statement recommends that this study should be performed immediately after birth, prior to the discharge from the hospital [16]-even though the grade of the hydronephrosis was not considered in any of these publications.…”
Section: Introductionmentioning
confidence: 99%
“…Hydronephrosis was assessed by the Society for Fetal Urology grading system or by the anterior-posterior diameter of the renal pelvis in the transverse plane [18,19]. Vesicoureteral reflux (VUR) was classified according to the International Reflux Grading classification [20].…”
Section: Methodsmentioning
confidence: 99%
“…Niu et al in a study regarding ureteral polyps as an etiological factor, evaluated 15 cases with hydronephrosis. They have examined UPJ with 3D images and concluded that although it is a important etiology in hydronephrosis, its diagnosis is difficult (21 a study regarding management of hydronephrosis, concluded that ultrasounds, voiding cystourethrograms, and nuclear renograms for diagnosis and surveillance are the best management approach in children (22). Kaya et al in a study regarding hydronephrosis etiology, evaluated 65 children with hydronephrosis in the department of pediatrics nephrology.…”
Section: Discussionmentioning
confidence: 99%